2017
DOI: 10.1002/glia.23191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol transport inhibitor U18666A on APP metabolism in rat primary astrocytes

Abstract: Amyloid β (Aβ) peptides generated from the amyloid precursor protein (APP) play an important role in the degeneration of neurons and development of Alzheimer's disease (AD). Current evidence indicates that high levels of cholesterol-which increase the risk of developing AD-can influence Aβ production in neurons. However, it remains unclear how altered level/subcellular distribution of cholesterol in astrocytes can influence APP metabolism. In this study, we evaluated the effects of cholesterol transport inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 79 publications
5
22
0
Order By: Relevance
“…Intriguingly, both membrane proteases, TMPRSS2 and ADAM17, partition primarily to the detergent‐resistant membrane domains, that is, lipid rafts of the plasma membrane 13,37 . While no formal evaluation for the expression and/or activity level of TMPRSS2 has been reported in NPC, it is suggested that the plasma membrane levels of ADAM17 are elevated in NPC, 38‐40 presumably due to the previously mentioned NPC‐related alterations in lipid rafts. As a result, it is possible to speculate that this elevated level of ADAM17 in the plasma membrane of NPC cells increases ACE2 shedding and counteracts TMPRSS2‐mediated entry‐favoring modifications, which grants these cells an increased “protection” against the viral binding.…”
Section: Npc‐related Perturbations In Ace2 and Adam17 Interfere With mentioning
confidence: 99%
“…Intriguingly, both membrane proteases, TMPRSS2 and ADAM17, partition primarily to the detergent‐resistant membrane domains, that is, lipid rafts of the plasma membrane 13,37 . While no formal evaluation for the expression and/or activity level of TMPRSS2 has been reported in NPC, it is suggested that the plasma membrane levels of ADAM17 are elevated in NPC, 38‐40 presumably due to the previously mentioned NPC‐related alterations in lipid rafts. As a result, it is possible to speculate that this elevated level of ADAM17 in the plasma membrane of NPC cells increases ACE2 shedding and counteracts TMPRSS2‐mediated entry‐favoring modifications, which grants these cells an increased “protection” against the viral binding.…”
Section: Npc‐related Perturbations In Ace2 and Adam17 Interfere With mentioning
confidence: 99%
“…In line with these effects of increased cholesterol in lysosomes, extraction with 2-hydroxypropyl-cyclodextrin (CDX) in AD models revealed a dual effect of CDX in modulating the mechanisms involved in AD pathology (Yang et al, 2017a ). While CDX enhanced lysosomal activity, it impaired autophagosome-lysosome fusion resulting in defective autophagy and clearance of Aβ fragments (Yang et al, 2017b ). Together, these findings strongly suggest that unlike NPC disease, the accumulation of cholesterol in lysosomes does not seem to be a characteristic feature of AD and that prolonged treatment with CDX should be carefully evaluated to avoid unwanted effects on autophagy.…”
Section: Role Of Intracellular Cholesterol In Neurodegenerationmentioning
confidence: 99%
“…Exocytosis of APP fragments generated at the endolysosomal compartments could either be a constitutive process or a consequence of intracellular accumulation due to impaired lysosomal degradation. Cholesterol sequestration by endolysosomes corresponds to decreased lysosomal clearance of APP fragments [ 60 ]. Lysosomal dysfunction is often linked with diminished autophagic flux, which is manifested in astrocytes expressing ApoE4 and correlates with accumulation of Aβ plaque [ 61 ], potentially exacerbating neuronal pathology.…”
Section: Amyloid Precursor Protein and Apoe Cross Paths In Endolysmentioning
confidence: 99%